Down-regulation of astrocytic sonic hedgehog by activation of endothelin ETB receptors: Involvement in traumatic brain injury-induced disruption of blood brain barrier in a mouse model. (June 2021) - Michinaga, Shotaro; Inoue, Ayana; Sonoda, Kyomi; Mizuguchi, Hiroyuki; Koyama, Yutaka
Abstract: In the adult brain, sonic hedgehog acts on cerebral microvascular endothelial cells to stabilize the blood-brain barrier. The expression of sonic hedgehog by astrocytes is altered during brain injury, and this change has been shown to affect permeability of blood-brain barrier. However, much remains unknown about the regulation of astrocytic sonic hedgehog production. Our results showed that endothelin-1 reduced sonic hedgehog mRNA expression and extracellular protein release in mouse cerebral cultured astrocytes, but had no effect in bEnd.3, a mouse brain microvascular endothelial-derived cell line. The effect of endothelin-1 on astrocyte sonic hedgehog expression was suppressed by an ETB antagonist BQ788, but was unchanged by the ETA antagonist FR139317. In cultured astrocytes and bEnd.3, endothelin-1 did not affect the expression of the sonic hedgehog receptor-related molecules, patched-1 and smoothened. In an animal model of traumatic brain injury, fluid percussion injury on the mouse cerebrum increased the expression of sonic hedgehog, patched-1, and smoothened. Repeated administration of BQ788 enhanced sonic hedgehog expression at 5 days after fluid percussion injury. Histochemical examination revealed sonic hedgehog expression in glial fibrillary acidic protein-positive astrocytes in the cerebrum after fluid percussion injury. Administration of exogenous sonic hedgehog and BQ788 suppressed Evans blue extravasation, an indicator of blood vessel permeability, induced by fluid percussion injury. The effects of BQ788 on fluid percussion injury-induced Evans blue extravasation were reduced by the administration of jervine, a sonic hedgehog inhibitor. Altogether, these results suggest that endothelin-1 down-regulates astrocytic sonic hedgehog to promote disruption of the blood-brain barrier during traumatic brain injury. Graphical abstract: Image 1 Highlights: Endothelin-1 decreases sonic hedgehog production in astrocytes through ETB receptors. In vitro fluid percussion injury increases sonic hedgehog production in astrocytes. ETB receptor antagonism promotes sonic hedgehog production in traumatic brain injury. ETB receptor antagonism reduces Evans blue extravasation in traumatic brain injury. Endothelin-induced down-regulation of sonic hedgehog may promote disruption of blood-brain barrier.